Inequalities in Job Loss and Income Loss in Sub-Saharan Africa during the COVID-19 Crisis - Ivette Contreras-Gonzalez; Gbemisola Oseni; Amparo Palacios-Lopez; Janneke Pieters; Michael Weber (Institute of Labor Economics (IZA), 2022)
We use high frequency phone survey data from Ethiopia, Malawi, Nigeria, and Uganda to analyze the impacts of the COVID-19 crisis on work (including wage employment, self-employment, and farm work) and income, as well as heterogeneity by gender, family composition, education, age, pre-COVID-19 industry of work, and between the rural and urban sector. We link phone survey data collected throughout the pandemic to pre-COVID-19 face-to-face survey data in order to track the employment of respondents who were working before the pandemic and analyze individual level indicators of job loss and re-employment. Finally, we analyze both immediate impacts, during the first few months of the pandemic, as well as longer-run impacts up to February/March 2021. We find that in the early phase of the pandemic, women, young, and urban workers were significantly more likely to lose their job. A year after the onset of the pandemic, these inequalities disappeared while education became the main predictor of joblessness. We find significant rural/urban, age, and education gradients in household level income loss. Households with income from non-farm enterprises were most likely to report income loss, in the short run as well as the longer run.
Keywords: J20; J10; I31; 330; COVID-19; employment; income; inequality; Africa